Does Profitability Moderate the Relationship Between Firm Size, Capital Structure, CSR, and Firm Value? - Wulan Retnowati; Apriyanti Apriyanti; Amaury Capdeville Chapuzet (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: This study aimed to determine the effect of firm size, capital structure, and corporate social responsibility (CSR) on firm value by using profitability as a moderation variable. It also incorporated control variables including liquidity in real estate, construction, and property companies recorded on the IDX (Indonesia Stock Exchange) from 2017 to 2021. Research Methods: With purposive sampling, 40 companies were selected for analysis. Furthermore, data collection was conducted through documentation studies and the data were further analysed by multiple linear regression. Results / Findings: The findings showed that the firm size possessed no effect on the firm value while capital structure affected the firm value. Additionally, CSR affected the firm value and profitability moderated the relationship between firm size and value. Profitability further moderated the relationship between capital structure and firm value but did not moderate CSR against firm value. Conclusions: The results indicated that firm size did not have an impact on the firm value while capital structure and CSR had a substantial impact on firm value. Profitability was also found to moderate the relationship between firm size and firm value, as well as the relationship between capital structure and firm value. However, profitability did not moderate the relationship between CSR and firm value.